Pork production on YouTube: frame and sentiment analysis - Karki, Anu; Qu, Shuyang; Masambuka-Kanchewa, Fally; Retallick, Michael; Lamm, Alexa J.; Lamm, Kevan; Sanders, Catherine E.; Byrd, Allison; Gabler, Nicholas (Frontiers in Communication, 2025)
IntroductionSocial media platforms increasingly influence public perceptions of agriculture by shaping narratives around food production. This study explores the portrayal of pork production on YouTube and the corresponding audience reactions, highlighting its role in shaping public discourse.MethodsGuided by the framing theory, the research examines 147 videos and 735 top comments to analyze media and audience frames alongside sentiments. Video titles, descriptions, and thumbnails represent media frames, while the top comments reflect audience frames. Frames are identified through literature review and sample analysis, with selected videos manually coded for frame presence. Sentiment analysis of textual elements is conducted using MaxQDA, and visual elements are coded manually.ResultsFindings show that information and technology of pork production, and entrepreneurship frames dominate media portrayals, emphasizing information sharing on production practices and business ventures. In contrast, audience responses often highlighted ethical concerns, particularly animal welfare, underscoring moral sensitivity in public discourse. Positive sentiments were prevalent across media and audience responses, though critical views remained significant. The strong alignment between media and audience frames and sentiments underscores the influence of strategic framing in shaping perceptions. Emotional appeals in videos are found to play a critical role in audience reactions.DiscussionThese findings suggest that transparent communication emphasizing ethical practices and technological advancements can effectively engage audiences. By aligning content with audience values and leveraging emotional connections, communicators can counteract misinformation, foster trust, and promote informed discussions about the pork industry. This study provides a framework for utilizing social media, specifically YouTube, to address public concerns while advancing transparency and trust in agricultural practices.